Upstream Operations in the Oil Industry: Rigorous Modeling of an Electrostatic Coalescer. (April 2017) - Rossi, Francesco; Colombo, Simone; Pierucci, Sauro; Ranzi, Eliseo; Manenti, Flavio
Abstract: This paper deals with a first-principle mathematical model that describes the electrostatic coalescer units devoted to the separation of water from oil in water-in-oil emulsions, which are typical of the upstream operations in oil fields. The main phenomena governing the behavior of the electrostatic coalescer are described, starting from fundamental laws. In addition, the gradual coalescence of the emulsion droplets is considered in the mathematical modeling in a dynamic fashion, as the phenomenon is identified as a key step in the overall yield of the unit operation. The resulting differential system with boundary conditions is then integrated via performing numerical libraries, and the simulation results confirm the available literature and the industrial data. A sensitivity analysis is provided with respect to the main parameters. The mathematical model results in a flexible tool that is useful for the purposes of design, unit behavior prediction, performance monitoring, and optimization.